2021
DOI: 10.1002/adma.202102055
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous 2D/3D Tin‐Halides Perovskite Solar Cells with Certified Conversion Efficiency Breaking 14%

Abstract: As the most promising lead‐free one, tin‐halides based perovskite solar cells still suffer from the severe bulk‐defect due to the easy oxidation of tin from divalent to tetravalent. Here, a general and effective strategy is delivered to modulate the microstructure of 2D/3D heterogeneous tin‐perovskite absorber films by substituting FAI with FPEABr in FASnI3. The introduction of 2D phase can induce highly oriented growth of 3D FASnI3 and it is revealed in the optimal 2D/3D film that 2D phase embraces 3D grains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
368
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(400 citation statements)
references
References 49 publications
6
368
2
Order By: Relevance
“…Yu et al recently achieved a PCE of 14.81% with a certified conversion efficiency of 14.03% for FASnI 3 -based inverted PSCs by adding 4-fluorophenethylammonium bromide (FPEABr) into the perovskite precursor solution to fabricate a 2D/3D mixed tin perovskite films. [120] They added different ratios of FPEABr in the precursor solution to effectively modulate the microstructure of 2D/3D heterogeneous perovskite film. It is observed that devices with 10% FPEABr showed the highest PCE.…”
Section: Fasni 3 -Based Pscsmentioning
confidence: 99%
“…Yu et al recently achieved a PCE of 14.81% with a certified conversion efficiency of 14.03% for FASnI 3 -based inverted PSCs by adding 4-fluorophenethylammonium bromide (FPEABr) into the perovskite precursor solution to fabricate a 2D/3D mixed tin perovskite films. [120] They added different ratios of FPEABr in the precursor solution to effectively modulate the microstructure of 2D/3D heterogeneous perovskite film. It is observed that devices with 10% FPEABr showed the highest PCE.…”
Section: Fasni 3 -Based Pscsmentioning
confidence: 99%
“…Tin-based halide perovskite materials have attracted much attention due to their low toxicity, suitable band gap, and their rapid improvement of the performance of photovoltaic devices [ 1 , 2 , 3 , 4 , 5 ]. Tin-based perovskite solar cells (TPSCs) show significant potential owing to their planar device structure, low-temperature solution fabrication process, and potential applications in flexible and tandem devices [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These methods involve changing the perovskite precursor solution concentration and temperature, optimizing the coating parameters such as the spin speed and time, tuning the annealing temperature of thin films. In addition to these methods, new techniques such as composition ( Kang and Park, 2019 ) and thermal engineering ( Srivastava et al, 2018 ), additive engineering in the perovskite precursor solution ( Tavakoli et al, 2019 ; Giuliano et al, 2021 ; Zhang et al, 2021 ), air-assisted drying ( Ding et al, 2019 ), humidity tuning ( Gangishetty et al, 2016 ), vapor-assisted annealing ( Sheng et al, 2015 ; Shi et al, 2015 ; Karlsson et al, 2021 ), and surface passivation layer capping ( Chen P. et al, 2018 ; Tavakoli et al, 2019 ; He et al, 2020 ; Yu et al, 2021 ) are also employed. To gain a deeper insight into this, we need to understand film optimization through the process of the crystal growth and design.…”
Section: Introductionmentioning
confidence: 99%